RETRACTED: Neuromodeling in horticulture and viticulture - Chetyrbok Petr; Kazak Anatoliy; Gallini Nadezhda; Rudenko Marina; Rudenko Andrey; Abramov Dmitry (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001